Thermal and -γ –Ray Irradiation Effects on the Ionic Conductivity of (LiCl)x(Montmorillonite)1-x - Purnama, Safei; Jahja, Aziz Khan; Sakuma, Takeshi (UI Scholars Hub, 2016)
Compositesof montmorillonite (MMT) - lithium salts have been prepared using a simple process of powders mixing followed by heating. The powders resulting from this method are expected to beionic conductors with a high ionic conductivity characteristics. This characteristics is also further improved by employing gamma-ray irradiation technique at specified irradiation doses. The best results were obtained for the (LiCl)0.5(MMT)0.5 composite with a room temperature ionic conductivity of 2.192 mS/cm, which then increases to 5 mS/cm after gamma irradiation at a dose of 400 kGy. This value is equivalent to the value of the ionic conductivity of current commercial rechargeable lithium battery, which is 10 mS/cm. However the commercial battery system is still employing an unsafe organic electrolyte. By employing this lightweight,inexpensive and high-temperature resistant ceramic montmorillonite, the final result of this Research and Development workt is expected to provide an alternative solid electrolyte system for rechargeable battery which is safer and more inexpensive especially for secondary battery technology development in Indonesia.